Free radicals level, antioxidative activity changes dynamic in patients with different brain vessels damage - Sutkovoy D. А.; Tsimeiko О. A.; Makarova T. А.; Huk А. P.; Trоyan А. I.; Sutkovoy А. D. (Ukrainian Neurosurgical Journal, 2005)
Under the conditions of pro- and antioxidative status destabilization considerable changes of brain vessels were observed, which caused serious breaks of blood circulation in the brain. The main subject of our study was the pro- and antioxidant activity state evaluation in patients with acute break of brain blood circulation of hemorragic and ishemic type. The oxidant activity increase already on the first stages of the process was established. In the patients with acute disturbance of blood circulation of ishemic type, the oxidant activity increased on 5–7th day of therapy, while in the case of hemorragic type — on 1st–2nd days. Both types of vascular pathology were characterized through decreased level of antioxidant, especially fermentative, activity. Neurosurgical intervention partially normalized the pro- and antioxidant status of the patients.